Why do two π-electron four-membered Hückel rings pucker? - McKee, William C.; Hofmann, Matthias (Organic letters, 2012)
Notwithstanding their two (i.e., 4n + 2) π electrons, four-membered ring systems, 1-4, favor puckered geometries (1a-4a) despite the reduction in vicinal π overlap and in the ring atom bond angles. This nonplanar preference is due to σ → π* hyperconjugative interactions across the ring (A) rather than to partial 1,3-bonding (B). Electronegative substituents (e.g., F in C4F42+) reduce the σ → π* electron delocalization, and planar geometries result. In contrast, electropositive groups (e.g., SiH3 in C4(SiH3)42+) enhance hyperconjugation and increase the ring inversion barriers substantially.